Pengaruh penggunaan model problem based learning terhadap peningkatan kemampuan penalaran mahasiswa pada mata kuliah kalkulus III - Ratna Rustina (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2015)
This research was conducted to provide an alternative learning model which can improve the ability of students ‘ reasoning. By giving the opportunity to students to be more active in the learning process, Problem Based Learning model was one of the alternatives to improve students ‘ reasoning in calculus III course. This research was quasi experimental research at the Siliwangi University Tasikmalaya to answer the main hypothesis: Problem Based Learning can improve the ability of students mathematical reasoning. The instruments used in this study consisted of mathematical reasoning tests in Calculus III. Research samples were taken randomly i.e. one experimental class and one control class. The data were processed by using the normalited gain test, t-test percentage presentation after all the requirenment of the test were met. The results of the analysis shows that there was a difference.